2023
DOI: 10.1002/jeab.844
|View full text |Cite
|
Sign up to set email alerts
|

The effects of note taking as a visual mediation strategy on the formation of equivalence classes

Abstract: A graphic organizer (GO) is a note-taking device with concepts and fill-in spaces that may enhance equivalence yields under suboptimal training and testing parameters (e.g., linear training, simultaneous testing, five-member all-abstract classes). We used a nonconcurrent multiple-probe design across eight adult participants to evaluate the effects of a treatment package consisting of abstract matching-to-sample baseline relations training (MTS-BRT) and GO-construction training. GOs were faded until participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…
Effective note taking may enhance learning outcomes for students and serve as a directly observable form of mediation within a test context. Frampton et al (2023) used stimulus fading to teach note taking in the form of a graphic organizer (GO) during matching-to-sample baseline relations training (MTS-BRT). Moderately high yields were observed with young adults despite the use of linear series training, abstract stimuli, and five-member classes.
…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…
Effective note taking may enhance learning outcomes for students and serve as a directly observable form of mediation within a test context. Frampton et al (2023) used stimulus fading to teach note taking in the form of a graphic organizer (GO) during matching-to-sample baseline relations training (MTS-BRT). Moderately high yields were observed with young adults despite the use of linear series training, abstract stimuli, and five-member classes.
…”
mentioning
confidence: 99%
“…Through a cognitive lens, note taking has been hypothesized to help students encode relevant information (Rahmani & Sadeghi, 2011) and relieve cognitive load by allowing students to use notes as a form of external storage (Manoli & Papadopoulou, 2012;Rahmani & Sadeghi, 2011;Stull & Mayer, 2007). From a behavioral perspective, the use of notes or a GO may be interpreted as a form of problem solving (Frampton et al, 2023;Skinner, 1984;Stromer et al, 1998). When presented with a question for which a correct response is not evoked (a problem), Skinner (1984) suggested that one may engage in a series of intermediate responses that function to produce additional stimuli (problem solving) such that eventually a response is occasioned that produces reinforcement (the solution).…”
mentioning
confidence: 99%
See 3 more Smart Citations